(untitled) (Estudos em Design, 2024)
With the development of the digital landscape and the expansion of video exhibition spaces, the term "audiovisual design" has emerged in commercial, academic, and literary spheres to define project specificities based on the consolidation of language and the audiovisual industry. In this context, we consider it relevant to investigate the development of the concept and eventually discuss and propose conceptual guidelines based on these findings. To achieve this, we first conducted an integrative literature review on the term "audiovisual design" and its related terms in publications in Portuguese and Spanish, using the Capes, Scopus, Web of Science, SciELO, and Google Scholar databases. We identified publications from 2003 to 2021. Subsequently, we performed a qualitative analysis of the results (content analysis), leading to the development of a conceptual synthesis based on the characteristics, functions, methodology, and context of Audiovisual Design.